2021
DOI: 10.3390/toxics9010015
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Selected Elements in the Microscopic Image of Pine Needles as an Effect of Cement and Lime Pressure within the Region of Białe Zagłębie (Central Europe)

Abstract: In this study, we present the results of microscopic observations of pine needles Pinus sylvestris L. collected in the area of cement-lime pressure in the south-western part of the Świętokrzyskie Mountains in the region of Białe Zagłębie. Images of scanning electron microscopy (SEM) confirm the presence of particles with a size of about 2 to 20 µm on the surface of the needles. Analysis using X-ray energy dispersion spectroscopy (EDS) allowed, in turn, to identify lead, iron, aluminium, calcium, and silicon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Kozłowski [29] and Szwed et al [30] have shown that calcium and magnesium are the main components of dust deposited from the atmosphere around areas of extraction and processing of mineral resources. Cement dust as well as soot and fine slag particles during the winter heating season are also carriers of toxic metals.…”
Section: Introductionmentioning
confidence: 99%
“…Kozłowski [29] and Szwed et al [30] have shown that calcium and magnesium are the main components of dust deposited from the atmosphere around areas of extraction and processing of mineral resources. Cement dust as well as soot and fine slag particles during the winter heating season are also carriers of toxic metals.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with the findings of previous studies as limestone dust and lead accumulation in tree plants significantly reduced growth and development ( Inkoom, 2019 ; Solgi et al., 2020 ; Antoniadis et al., 2021 ). For limestone dust, overall photosynthetic reduction, detachment of premature leaves, leaf injuries, and limitation in growth and photosynthetic pigments are the major phenomena reported in various tree species ( Inkoom, 2019 ; Solgi et al., 2020 ; Szwed et al., 2021 ). Additionally, the maximum reduction in photosynthetic rate, stomatal conductance, transpiration rate, and evapotranspiration rate was reported in C. lancifolius followed by E. camaldulensis and B. ceiba , which demonstrated that B. ceiba and E. camaldulensis tree species are more effective bioindicators to limestone dust and Pb toxicity than C. lancifolius tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have reported the potential tree species for the removal of limestone-oriented dust pollution ( Panichev and McCrindle, 2004 ; Kończak et al., 2021 ). For instance, Szwed et al. (2021) reported that pine needles are decent bioindicators of limestone dust pollution due to the unique chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…It is valuable to compare identified elements found in our studies with the pollutants in other parts of Poland found by other researchers Szwed et al (2021). studied Pinus sylvestris L. needles grown in the southwestern part of the Świętokrzyskie Mountains in the Białe…”
mentioning
confidence: 85%
“…However, pine needles have been used as bioindicators since the end of the 20th century (Ericsson et al 1989). They are used to specify the atmospheric pollution in other parts of Poland (Parzych and Jonczak 2014;Szwed et al 2021), as well as all over the world e.g., in the Republic of Korea (Chung et al 2021), Finland (Pöykiö and Torvela 2001), Croatia (Juranovic ´Cindric ´et al 2019), Lebanon (Baydoun et al 2015) and others. Data presented in this paper were compared to previously published research.…”
Section: Introductionmentioning
confidence: 99%